Physical and sensory evaluation of cookies with cocoa bean, rice and wheat flours (Research, Society and Development, 2022)
It is growing the demand for alternative flours to wheat in bakery products. The cocoa bean shell flour (CFC), also known as cocoa bran, is a residue of chocolate industrialization, rich in fiber, nutrients and gluten-free becoming a potential substitute for wheat flour (WF), as well as rice flour (RF), known for its low allergenicity.  Thus, the objective was to develop cookies from cocoa, rice and wheat flours and evaluate the effect of the mixture on the physical characteristics and product acceptability. For this, seven cookie formulations were made following the simplex-centroid design (primary, binary and ternary mixtures of the components CFC, RF and WF). In the cookies, hardness, color (L*, ºHue, Chroma*) and purchase intention were determined. The intermediate hardness was observed in the cookies elaborated with CFC, can be justified, according to the literature by its high content of fibers present in the flour, while RF contributed for the softness of the cookies and WF for harder cookies. The presence of CFC was associated to darker cookies and with lower purity of color in relation to the other flours (RF and WF) that originated lighter cookies, golden and with higher purity of color, what was already expected by the distinction of color among the flours. The cookies in the formulations with higher concentration of CFC (50% and 100%) showed antagonistic effects on the purchase intention, contrary to the wheat and rice flours. It was found that the CFC employed in up to 33% of the flour base gives origin to cookies with adequate physical and sensorial characteristics, and can be used in baking.